Effets des politiques antidopages en cyclisme sur route en 2009. Le cas de la France - Brissonneau, C.; Ohl, F. (Movement & Sport Sciences - Science & Motricité, 2016)
Based on a contract for WADA, this article focuses on the transformation of French public policy on doping after Festina scandal and its effects on the life of cycling professionals. We first focus on the emergence and the evolution of French public policies against doping in cycling. Then the article attempts to qualitatively observe the effects of policies on cyclists representations. The objective is to understand how the cycling culture is evolving. This article is based on 39 interviews with new and seasoned professionals, as well as ethnographic observations over a dozen years.